Use Best Practices to Optimize Filter Performance. Issue 11 (1st November 2015) - Martin, Barb; Linder, Kevin
Abstract : Filtration is an essential component of a multibarrier approach to safe drinking water. Optimized filter performance and maintenance of filter integrity will help protect public health.